2015
DOI: 10.1111/jocn.12756
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the transition experiences of students entering into preregistration nursing degree programs with previous professional nursing qualifications: an integrative review

Abstract: The demand for health care is growing and there remains a shortfall of registered nurses. Nurses with professional qualifications (nondegree) are an important pool of professionals from which to increase registered nurse numbers and address workforce sustainability issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
(152 reference statements)
1
11
0
1
Order By: Relevance
“…Previous research has clearly identified the challenge of retaining students in their first semester or first year at University [25,26]. Universities are responding to this challenge by initiating transitional supports centrally, at Faculty or School levels and within programs or courses [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has clearly identified the challenge of retaining students in their first semester or first year at University [25,26]. Universities are responding to this challenge by initiating transitional supports centrally, at Faculty or School levels and within programs or courses [11].…”
Section: Discussionmentioning
confidence: 99%
“…At Orientation, students were provided with an overview of the Senses of Success Framework [16] and this made explicit the expectations that learning is co-created and students have a responsibility to develop academic skills and seek help when needed. Orientation has been associated with University success [26] and non-attendance at Orientation may contribute to the students starting to feel isolated or ‘left behind’ and may account for some of the participants' experiences of being bewildered and unable to locate or access support.…”
Section: Discussionmentioning
confidence: 99%
“…[7] For non-traditional nursing students, practicum experiences, where attendance at clinical sites for consecutive days and weeks at a time is required, can be especially challeng-ing. [8][9][10] Yet, it is often their practicum experiences that most help adult students become socialized into a new professional nursing role [11] and to re-imagine their professional identities in new ways. [12] Mentoring approaches that experienced clinical instructors believe are effective can make an important difference to these students, but they are seldom disseminated beyond individual educational institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Um conceito voltado para o contexto do estudante de enfermagem, que vivencia situações adversas em todo processo de formação, ainda precisa ser melhor esclarecido, não existindo um conceito único entre os estudos (Thomas, Revell, 2016;Aburn, Gott, Hoare, 2016). Ainda, estratégias de apoio para fortalecimento da resiliência entre esses estudantes, desde o início da graduação pode ser um ponto de partida útil para superar os desafios durante o curso de enfermagem (Tower et al, 2015).…”
Section: Resiliência Em Estudantes De Enfermagemunclassified